Why does emissions trading under the EU Emissions Trading System (ETS) not affect firms' competitiveness? Empirical findings from the literature - Eugénie Joltreau; Katrin Sommerfeld (Climate Policy, 2018)
Environmental policies may have important consequences for firms' competitiveness or profitability. For the European Union Emissions Trading System (EU ETS) the empirical literature documents that significant emissions reductions have resulted from it. Surprisingly, however, the literature shows that there have been hardly any concurrent negative effects on firms' competitiveness during the first two phases of the scheme (2005–2012). We show that the main explanations for the absence of negative impacts on competitiveness are a large over-allocation of emissions allowances leading to a price drop and the ability of firms to pass costs onto consumers in some sectors. Cost pass-through combined with free allocation, in turn, partly generated windfall profits. In addition, the relatively low importance of energy costs indicated by their average share in the budgets of most manufacturing industries may have limited the impact of the EU ETS. Finally, small but significant stimulating effects on innovation have been found so far. Several factors suggest that over-allocation is likely to remain substantial in the upcoming periods of the scheme. Therefore, we expect to see no negative competitiveness effects from the EU ETS in Phases III and IV (2013–2030).
Keywords: Q52; Q58; D22; 330; Cap and trade system; EU ETS; firm-level competitiveness